Metabolites of Astragalus membranaceus and their pro-apoptotic and cytotoxic activities: insights into targeted metabolic pathways - Liu, Jie; Wang, Dongwei; Ren, Na; Zhang, Li; Wang, Ting (Frontiers in Pharmacology, 2025)
Astragalus membranaceus (Astragalus), a traditional Chinese herbal medicine, is well known for its immunomodulatory effects. Recent studies have demonstrated that Astragalus exhibits antiviral, anti-inflammatory, anti-aging, anti-atherosclerotic, antioxidant, and immune-enhancing activities, as well as pro-apoptotic and cytotoxic effects on tumor cells. It is increasingly used as an adjuvant therapy in oncology. The mechanisms underlying its pro-apoptotic and cytotoxic activities include inhibition of tumor cell proliferation and migration, modulation of tumor-associated metabolic pathways, induction of tumor cell apoptosis, cell cycle arrest, regulation of autophagy, targeting of the tumor microenvironment, inhibition of neo-angiogenesis, and enhancement of host immunity. This review provides a comprehensive summary of the active metabolites of Astragalus and their pro-apoptotic and cytotoxic mechanisms, with a focus on metabolic regulation, offering a theoretical basis for its rational application in tumor therapy. Future research aimed at precise metabolite-guided interventions could improve patient outcomes and quality of life.